Prevalence and prognosis of multimorbidity in heart failure with mildly reduced ejection fraction - Reinhardt, Marielen; Behnes, Michael; Abumayyaleh, Mohammad S. A.; Bertsch, Thomas; Görtz, Michelle; Abel, Noah; Schmitt, Alexander; Lau, Felix; Dudda, Jonas; Weidner, Kathrin; Akın, Ibrahim; Schupp, Tobias (Clinical research in cardiology, 2026)
Related to ongoing demographic, the number of patients with cardiac and non-cardiac comorbidities increases. Heart failure with mildly reduced ejection fraction (HFmrEF) represents a heterogeneous population with diverse clinical profiles. The study investigates the prevalence and prognostic impact of multimorbidity in patients hospitalized with HFmrEF.